Chemical Properties and Breakthrough Adsorption Study of Activated Carbon Derived from Carbon Precursor from Carbide Industry - Husain, Nursyuhani Che; Zawawi, Nurul Athirah; Hamzah, Fazlena; Mohd Rodhi, Miradatul Najwa; Veny, Harumi; Ariyanti, Dessy; Mohidem, Nur Athikah (ASEAN Journal of Chemical Engineering, 2023)
The residual carbon from the carbide industry in Malaysia has been explored as a precursor in activated carbon (ACs) processing via chemical activation with potassium hydroxide (KOH). The residual carbon from the carbide industry consists of high fixed carbon content and is a sustainable source of raw material, making it a promising precursor for ACs processing. However, the synergy between activation temperature with impregnation ratio has yet to be well explored for precursors from carbide processing. Thus, in the present work, impregnation ratios from 1:1 to 1:5 and temperature for the activation process from 300°C to 700°C were examined in the ACs processing. The impact of these factors was evaluated towards the chemical characteristic of the derived ACs, such as pores and surface morphology, functional groups, and thermal profile. The finding indicated that the ratio of as-received carbon /KOH from 1:1 to 1:5 provided ACs with BET surface areas of 130 – 458 m2 /g and micropores content of 19 – 25.75%. The results suggested that the highest BET surface area in this range of study was 458.15 m2 /g at an activation temperature of 700oC and an impregnation ratio of 1:1. Then the developed ACs were further evaluated in carbon dioxide (CO2) adsorption using breakthrough CO2 adsorption. The breakthrough time and CO2 adsorption rate capacity were calculated as 70 s and 0.175 mmol/g, respectively. This finding indicated that as-received carbon precursors from the carbide industry could be explored as one of the potential materials in ACs development, forming the microporous structure during KOH activation and encouraging the binding of CO2 molecules in CO2 capture.